Fish Community in Serayu River, Banyumas Residency, Central Java, Indonesia - Susanto, Susanto (EDUCARE, 2015)
ABSTRACT: This research was purposed to reveal and discover fish community in Serayu river at Banyumas Residency, Central Java, Indonesia. Research was done in two years which replicated each 3 months, since October 2009 till July 2011. Data analysis including: aquatic physical and chemical parameter and plankton species variation, fish abundance, fish species diversity and domination, age structure, condition factor, fecundity, Gonade Growth Level (GGL), Gonade Growth Index (GGI), and environmental factor and fish community structure relationship. Analysis done in this research were diverse analysis with software: Plymouth Routines in Multivariate Ecological Research (Primer), Cluster, and Multi Dimensional Scalling (MDS). During research fishes caught were as many as 3,871 fishes divided to 29 species, 20 families, and 11 ordos. Aquatic qualities factor including aquatic physical and chemical parameters and plankton species variation in Serayu river at Banyumas Residency were in good condition and suitable for fishes life. Cyprinidae family found as most varied species and most founded species in individual number at Serayu river in Banyumas Residency. There were low species diversity, but there werenât found any dominance. Fish abundance in Serayu river increasing toward downstream, but discovered otherwise with fish diversity. Fish community in area toward upstream from Serayu Adjustable Dam differs with fish community in area toward downstream from Serayu Adjustable Dam. Serayu Adjustable Dam existence causing on decreasing fish species abundance and diversity in Serayu river at Banyumas Residency; thus, decrease fish community quality both in area before and after the dam. Fish growth pattern and reproduction profile in Banyumas Residency are not ideal.KEY WORDS: Fish community, abundance, diversity, domination, upstream and downstream, Serayu river, Serayu Adjustable Dam, and pattern and reproduction.About the Author: Dr. Susanto is a Senior Lecturer at the FKIP UMP (Faculty of Education and Teacher Training, Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto City, Central Java, Indonesia. For academic purposes, the author can be contacted via e-mail at: susanto280266@gmail.comHow to cite this article? Susanto. (2015). âFish Community in Serayu River, Banyumas Residency, Central Java, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.8(1) August, ppâ¦. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Â Chronicle of the article: Accepted (July 15, 2015); Revised (August 3, 2015); and Published (August 25, 2015).